Menyoal “Kerugian BUMN” Dalam PP Nomor 23 Tahun 2022 Tentang Pendirian, Pengurusan, Pengawasan, dan Pembubaran BUMN - Siti Nurhalimah (UIN Syarif Hidayatullah Jakarta, 2022)
BUMN is always in the spotlight. BUMN promotes public welfare and owns at least 51% of the state's shares. This 51 percent share creates the impression that BUMN's riches are the state's wealth, hence its loss is the state's loss. BUMN losses are linked to corruption. The legality of the loss is being disputed. There's nothing improper because of the legal position of BUMN assets. Currently, the government has changed PP No. 45 of 2005 about the Establishment, Management, Supervision, and Dissolution of SOEs to add